Informal caregiver burden among stroke patients in east-coast Peninsular Malaysia: a short-term longitudinal study - Suliman, Mohd Azmi (2023)
Background: Stroke is a leading cause of death and disability worldwide. Many stroke survivors require assistance for basic activities of daily living (ADL) and instrumental activities of daily living (IADLs). Stroke attacks happen suddenly, and family members must act as informal caregivers swiftly. Unfortunately, many caregivers feel upset or burdened during caring for stroke survivors. Studies on caregiver burden are vital in helping policymakers prioritise support and researchers develop interventions targeting stroke survivors and caregivers. This study aims to measure the burden among informal caregivers for stroke survivors in East Coast Peninsular Malaysia. Method: In this research, three related research articles were produced. First, a bibliometric analysis was done to measure the academic production and collaboration of the author, institutions, and countries. The publications with a title containing “stroke” and “caregiver” were searched using Clarivate’s Web of Science database. Second, a descriptive analysis was done to describe the distribution of stroke survivors, informal caregivers, and the burden of stroke caregivers. Stroke survivors and their caregivers were recruited from three East Coast Peninsular Malaysia hospitals. The caregiver burden was measured using the Malay version of Zarit Burden Interview (MZBI) and the Malay version of Caregiver Appraisal of Function and Upset (Malay-CAFU) via phone call four times within the first three months post-discharge. Third, using the same data, an inferential analysis was done using a linear mixed effect model to estimate the stroke caregiver burden trends and the effect of stroke survivors’ dependency level on the burden trajectory. Result: In the bibliometric analysis, it was found that 678 publications dated from 1989 to 2022 with titles containing the terms “stroke” and “caregiver”. The publications were primarily published in the English language. The publications mainly were produced in the USA (28.6%), by The University of Toronto (9.5%), in ‘Topics in Stroke Rehabilitation’ journal (5.8%), and the most productive author was Tamilyn Bakas (3.1%). For the caregiver burden, 85 stroke survivors and 155 informal caregivers were recruited. On average, the stroke survivors had two caregivers, mainly female (58.1%). In the first three months, the burden was reduced, with the mean (SD) of MZBI reduced from 27.42 (12.73) in the first week to 17.77 (11.20) in the third month, while IADL Malay-CAFU Upset reduced from 1.14 (0.94) to 0.62 (0.64) and ADL Malay-CAFU from 1.36 (1.00) to 0.78 (0.65) in the same period. When accounted for the clustering effect using a linear mixed effect model, the MZBI shows a reduction from 1-week post-discharge to 3-month [beta = -10.76 (95% CI = -11.94, -9.57)], and Malay-CAFU at 3-month [beta = -0.68 (95% CI = -0.80, -0.57)]. The burden was higher among caregivers with dependent stroke survivors; however, the rate of reduction of burden was not significantly different. Conclusion: The studies on stroke caregivers were extensive; however, ongoing studies on the field are essential. Areas of interest in the field include the experience of stroke caregivers, the level and the determinant of burden and the interventions in managing the burden. Many stroke survivors were taken care of by several informal caregivers, especially family members. However, the caregivers may feel burdened while giving care; however, the burden is usually reduced in the first three months post-stroke. Therefore, policymakers and healthcare providers should initiate support and interventions for caregivers and stroke survivors as early as at the time of diagnosis.